Analisis Pemanfaatan Aplikasi Akuntansi Berbasis Android (SI APIK) Untuk Menunjang Pelaporan Keuangan UMKM - I Putu Yudhi Antara Satyawan; I Putu Fery Karyada; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2023)
In this digital era, there are still many MSMEs that have not made financial reports and are still doing financial records manually. This study aims to identify whether the application of SI APIK can assist in supporting financial reporting in the Teh Poci Fresh business. This type of research is descriptive qualitative research, with data collection techniques in the form of observation, interviews and documentation, this research is carried out by reporting analysis through the application of the APIK SI application, as well as analyzing the benefits and constraints of the APIK SI application implementation. The results obtained that the application of SI APIK can help meet the needs of accounting information systems in SMEs. The Si Apik application helps MSMEs in carrying out accounting records and making good financial reports and in accordance with applicable rules.